2008
DOI: 10.1016/j.cdp.2008.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking and risk of recurrence for squamous cell cancer of the anus

Abstract: Objective Squamous cell cancer of the anus is associated with multiple risk factors, including infection with human papillomavirus, immunosuppression, chronic inflammation, and tobacco smoking, although there is little data on these factors for the prediction of recurrent disease. Here, we evaluated the risk of recurrence and mortality of anal carcinoma in association with tobacco smoking. Methods We conducted a retrospective review of cases of anal carcinoma from two local hospitals. We obtained information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…Tobacco smoking is a well‐established risk factor for HPV‐associated anogenital cancer. It was recently shown that smokers with anal cancer are more likely to die from recurrence than nonsmokers, with 45% of smokers being dead compared with only 20% of nonsmokers by 5 years after treatment 33 . In line with this, only one patient with canal ASCC had long‐term response to CRT, and this patient had never smoked.…”
Section: Discussionmentioning
confidence: 65%
“…Tobacco smoking is a well‐established risk factor for HPV‐associated anogenital cancer. It was recently shown that smokers with anal cancer are more likely to die from recurrence than nonsmokers, with 45% of smokers being dead compared with only 20% of nonsmokers by 5 years after treatment 33 . In line with this, only one patient with canal ASCC had long‐term response to CRT, and this patient had never smoked.…”
Section: Discussionmentioning
confidence: 65%
“…As such, little is known about the etiology of the adenocarcinoma type. Smoking is reported as a risk factor that correlates with anal cancer, especially in those with HPV infections [122,123]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the role of smoking in the development of perianal BCC has not yet been determined. 9 Perianal BCC cases have also been reported in patients receiving pelvic radiotherapy due to genitourinary system malignancies. 1,2,5 In a study performed by Eliezri et al, HPV DNA type 16 infection has been shown in biopsy specimens of BCCs developed in sun exposed areas, such as head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…10 In another study that investigated the role of HPV in the etiology of BCC, no relationship was found. 9 The presented patient had no history of pelvic radiotherapy or chronic trauma and showed no HPV DNA with PCR analysis in the biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%